The Sustainability of the Popular House in Saharan Human Settlements - Nawal BENSLIMANE; Ratiba Wided BIARA; Mohammed BENSAFI (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Hot desert regions, like ALGERIAN SAHARA, are very challenging in terms of building energy consumption. The energy demand needs to be reduced significantly before employing renewable energy, and a way to achieve that is through applying vernacular construction techniques and materials.However,a few traditional architecture have survived and among those few that have survived, many have been modified in ways that have destroyed the climate responsive properties of such buildings. The combination of inappropriate architectural practices and the use of active systems in the provision of climatic comfort conditions now constitute a very real threat to the sustainable development. In the Algerian Sahara, Ksourian architecture is the product of a mass culture nourished by everyday life, local values, environment and local engineering. This habitat is expressed by the spontaneity of its tissue, oasis ecosystem, and its colors that blend in. Today, the Ksours of south Algéria has become a real open-air museum, testifying to an architectural heritage of national importance. Today, these Ksours has become a real open-air museum, testifying to an architectural heritage of national importance, before the brutal penetration of "modern" urbanization.